2013
DOI: 10.1080/02673843.2013.779587
|View full text |Cite
|
Sign up to set email alerts
|

Equine-assisted activities and the impact on perceived social support, self-esteem and self-efficacy among adolescents – an intervention study

Abstract: In this project, we examined the effect of a 4-month intervention with horses on perceived social support, self-esteem and general self-efficacy among Norwegian adolescents aged 12–15 years. The intervention took place at farm-based stables and included work with the horses and riding. A waiting-list crossover design was used and the participants answered questionnaires at three time periods. Study I (N = 49) examined the effect of the intervention compared with the control group. Study II (N = 41) examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 64 publications
4
70
0
4
Order By: Relevance
“…Several studies found an association between television watching and subjective assessment of daytime tiredness(34, 54, 66), while one study found no association(51). Twelve studies included other measures of sleep outcomes and 75% of the studies found significant associations.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found an association between television watching and subjective assessment of daytime tiredness(34, 54, 66), while one study found no association(51). Twelve studies included other measures of sleep outcomes and 75% of the studies found significant associations.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are promising and suggest that pet ownership should be investigated as a strategy to increase self-esteem in developing youths. Findings that support this include research carried out using a horse therapy program; although no intervention effect was found on self-esteem, an increase was found in perceived social support in comparison with the control group [63]. Pets such as horses and dogs are most likely to increase social circles and the number of human contacts, and if so, could increase emotional health outcomes such as self-worth and self-esteem.…”
Section: Discussionmentioning
confidence: 96%
“…Mutual interaction with animals is found to provide a feeling of support because it creates an experience of connectedness (Brown, 2007). Social support is seen as an important factor in interactions with the horse among at-risk adolescents (Burgon, 2011) and even among a normal group of adolescents (Hauge et al, 2014). Overall, the theories connected to interaction with animals have been less subjected to scientific studies.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…By using behavior as a quantitative and objective measure, as done in the study of Hauge et al (2014) who registered the behaviors of horses in interaction with adolescents, we can get a better picture of which behavioral interactions stimulate humans the most. This could then be used in developing and refining the types of interactions used during intervention.…”
Section: A Relatively New Approach: Ethologymentioning
confidence: 99%